Design and Implementation of IoT-based Digital Notice Board using Arduino Uno (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
In this paper, the implementation of simple and IoT based wireless notice board is presented. Theproposed system uses Wi-Fi for communicating with cloud data base. The idea of digital notice boardand it’s working starts from pushing a message to cloud using an android mobile. At the received endaArduino Uno with a valid internet connection is setup is deployed and it is ready to receive themessages. Whenever it receives a new message it alerts the LCD display connected to it and itdisplays the message on LCD display.